High‐Frequency Ultrasonography for Classifying Lymphatic Sclerosis Types in Patients With Lymphedema - Xiaoxue Chen; Shufang Yuan; Liping Chen; Lanjing Wu; Chenyang Zhao; Yi Chen; Nan Zhuang; Longbiao Yu; Jingjing Wen; Pengzhou Huang; Zhengming Hu; Zhegang Zhou; et al. (Journal of Clinical Ultrasound, 2026)
ABSTRACT Background To identify predictive ultrasonic factors and establish cutoff values for assessing sclerosis severity and selecting appropriate lymphatic vessels for lymphovenous anastomosis (LVA). Methods We enrolled 22 patients with extremity lymphedema undergoing LVA (53 lymphatic vessels). Sclerosis severity was determined preoperatively by ultrasonography and intraoperatively using a surgical microscope; the findings were stratified by NECST (normal, ectasis, contraction, and sclerosis type) classification. Demographic and ultrasonographic data, including lymphatic vessel inner and outer diameters (Id and Od, respectively), Id/Od ratio, and wall thickness, were analyzed. Results Although NECST classifications for ultrasonographic and surgical observations exhibited discrepancies, ultrasound findings showed high overall accuracy (71.7%), with strong correlation ( r = 0.652) and moderate agreement ( k = 0.554) with intraoperative results. For ultrasound‐based classification, Id and Id/Od ratio of 0.43 mm and 34.1% were the suggestive values for predicting ectasis type, with the area under the curve (AUC) values of 0.843 and 0.842, respectively. For surgical evaluation‐based classification, Id and Id/Od ratio of 0.269 mm and 41% were the suggestive values for predicting ectasis type, with both AUC values > 0.8. These results were significant ( p < 0.05). Conclusion Ultrasonographic parameters could help identify ectasis type of lymphatic vessels in patients with extremity lymphedema.